PRONUNCIATION ERROR IN ED-ENDING: A CASE STUDY AMONG SCOOTER STUDENTS AT PARE KEDIRI - Alfin Fuji Hidayati (Arkhais - Jurnal Ilmu Bahasa dan Sastra Indonesia, 2021)
A common issue to imitate the native speaker is still being a trending discussion for the beginner of English foreign learner. They are very enthusiastic to reproduce how the native speaker speaks. It is natural that we are as foreign language learners cannot 100 % imitating native speakers’ pronunciation. It is proven by four students which pronounce the words ended by –ed ending. Beside of attempting native speakers’ pronunciation is quite hard especially for the beginner of EFL. It is also significant to identify that not all –ed ending can be produced as [-d or –ed] ending, it can be [t]. By conducting this research, it is shown that the level of students’ mastery in pronouncing –ed ending needs improvement. This study displayed that the difficult of –ed ending type was in special pronunciation. Meanwhile, the easiest one was –ed ending after a voiceless consonant apart from [t].